2007
DOI: 10.1086/519221
|View full text |Cite
|
Sign up to set email alerts
|

Combining Evidence of Natural Selection with Association Analysis Increases Power to Detect Malaria-Resistance Variants

Abstract: Statistical power to detect disease variants can be increased by weighting candidates by their evidence of natural selection. To demonstrate that this theoretical idea works in practice, we performed an association study of 10 putative resistance variants in 471 severe malaria cases and 474 controls from the Luo in Kenya. We replicated associations at HBB (P=.0008) and CD36 (P=.03) but also showed that the same variants are unusually differentiated in frequency between the Luo and Yoruba (who historically have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 45 publications
1
67
0
Order By: Relevance
“…Other factors such as population structure and chance, as well as the experimental design or the phenotype(s) of malaria diagnosed in a given study, may impact the conclusions. Efforts to use genomics approaches and genome-wide association analysis have been initiated (Ayodo et al, 2007;Timmann et al, 2007;The Malaria Genomic Epidemiology Network, 2008;Jallow et al, 2009;Eid et al, 2010) and some new regions of potential malaria resistance have been identified.…”
Section: Resistance Mutantsmentioning
confidence: 99%
“…Other factors such as population structure and chance, as well as the experimental design or the phenotype(s) of malaria diagnosed in a given study, may impact the conclusions. Efforts to use genomics approaches and genome-wide association analysis have been initiated (Ayodo et al, 2007;Timmann et al, 2007;The Malaria Genomic Epidemiology Network, 2008;Jallow et al, 2009;Eid et al, 2010) and some new regions of potential malaria resistance have been identified.…”
Section: Resistance Mutantsmentioning
confidence: 99%
“…Here, we genotyped G1 and G2 in the Yoruba from West Africa (Nigeria) and Luhya, a tribe in Eastern Africa (Kenya) that is genetically very similar to the Yoruba across the genome [fixation index (F st ) = 0.008] (25). We compared frequency differences using a statistical test for differentiation under a neutral model of genetic drift that accounts for random variation in allele frequency (Methods) (26). Of all 1,440,616 markers from HapMap3 that we compared across the genome in the two tribes, none were as differentiated between the two tribes as G1 (P = 5.11 × 10 −7 ) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals were genotyped for the G1 and G2 variants using Sequenom iPlex; rs73885319 was used as a proxy for G1 (r 2 between rs73885319 and rs60910145 is nearly one). The East African populations genotyped in this study are described in the work by Ayodo et al (26). The West African populations genotyped in this study have been previously described (41,42), and the samples were originally obtained from participants in a genetic epidemiology study of type 2 diabetes in West Africa (the Africa America Diabetes Mellitus Study) (43).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility to infection, like any other complex trait, is multifactorial and has a significant heritable component. Genomewide association (GWA) approaches have been extended to mapping the genetic architecture underlying susceptibility to infectious diseases (1)(2)(3)(4)(5), but only hemoglobin mutations and a handful of other loci conferring risk or protection to malaria have been identified (5)(6)(7)(8). There has also been no explicit effort to characterize the effects of host regulatory variation, polygenic inheritance, and genotype-by-infection interactions on malaria phenotypes in vivo.…”
mentioning
confidence: 99%